Implementasi pembelajaran interkultural pada Bahasa dan Budaya Tiongkok di kelas mandarin: artikel konseptual - Lukman, Diva Sania; Nida, Alifa Khoirun; Sunarti, S (Fakultas Sastra Universitas Negeri Malang, 2022)
The link between language and culture affects how a person communicates. How someone speaks can reflect that person's identity. Language skills and cross-cultural knowledge are also needed to create good communication. Mandarin itself is a representation of Chinese culture. Intercultural learning which is always related to language and culture is important for the learning process in Mandarin class because it can help students to understand both Indonesian and Chinese cultures. Mandarin is also an important language in the international world which indirectly increases people's interest in Chinese culture. The purpose of this learning itself is for students to understand correctly the pattern of language and the concepts of foreign cultures they are learning. In this case, a Mandarin teacher who masters the Mandarin language and culture will be an important aspect in the implementation of intercultural learning in the Chinese language and culture.